Association of Infant and Young Child Feeding (IYCF) Practices With Nutritional Status of Slum Residents of Lahore - S. M. Umar Kazmi, M. Imran Hussain, W. Ahmed, Momina Najeeb, A. Gul Memon, Saleh Shah,F. Chaudhary,S. Mengal, R. Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
This world which is now a changed and highly advanced version of people is really ambitious to know about calories and nutrients intakes of its people. Abnormal intake of food is that condition which is non-reversible and also has serious devastating effect on population of each group of age. But if we consider its effect on children, that is highly complicated and such as growth retardation, severe body muscle depletion and insufficiencies of necessary nutrients that results serious bodily and mental retardation for long period of time. Awkwardly, our Pakistan is the country that has to face these types of miseries related to newborn child nutrition status and health problems. These problems are increasing day by day due to inappropriate check and balance of nutrients intake of this age group by the government and also by the parents too. Survey of Pakistan that held in two thousand and eleven indicated that approximately 44% of all young child are facing growth retardation and 15% are underweight. According to this survey, 50% kids have iron deficiency and most probably 33% are facing iron deficiency related health problems. Approximately two fourth of population are facing difficulty of food shortage that lead to poor life standard and poor health. Total evaluation of this report stated that twenty tree to thirty two million inhabitants of Pakistan living in slum areas. International data (MICS (UNICEF) is conferringthat rate of early breastfeeding in Pakistan is 18%. There is a need to assess the nutritional status of children aged less than 2 years in light of IYCF practices of their mothers residing in slum areas of Lahore. Keywords: Malnutrition, infants, young child, feeding practices